PkM Pendampingan Tata Kelola Taman Pendidikan Al-Qur’an (TPQ) untuk Meningkatkan Kualitas Manajemen Pendidikan - Devi Suci Windariyah; Maskud Maskud (Universitas Nurul Jadid, 2023)
The purpose of this community service activity is to foster the commitment of Al-Qur'an Education Park (TPQ) teachers and the community to improve the management quality of the Al-Qur'an Education Park (TPQ). Apart from that, it is also to mobilize the surrounding community to be aware of the importance of managing TPQ governance for the further development of TPQ. The dedication method used is participatory action research (PAR), which is a research method whose implementation is carried out with the community. The three main pillars of PAR are research methodology, action dimensions, and participation dimensions. The results of this activity are: 1) mentoring on TPQ education management; 2) strengthening training on active learning at TPQ; and 3) socialization of the application of learning attendance and media connecting students’ achievements.